Strategic Lawsuits Against Public Participation (SLAPPs), 1987-1990: (United States) - Canan, Penelope ([Verlag nicht ermittelbar], 1992)
The objectives of this data collection were to capture the histories of complex, multiparty, political legal disputes, to measure political "chill," and to test a model of crossinstitutional disputing. A "Strategic Lawsuit Against Public Participation" (SLAPP) was defined as a lawsuit filed against citizens or groups exercising the right to petition the government. Each case violated the First Amendment right "to petition the government for a redress of grievances." The Petition Clause, as it is called, is a fundamental civil right, guaranteeing and encouraging citizen involvement in all aspects of American political decision-making and governance. The collection includes information on the petition action, political context, amount of award or settlement, specific damages requested (no money vs. a specified amount), attorney status, amount of court costs, attorney fees, interest, and number of individuals and organizations involved in the suit. Also included are several sociodemographic variables describing the parties to the litigation, such as marital status, employment, occupation, county and state of residence, political party orientation and membership, and interest group membership.